Legal and institutional arrangements for damage caused by wildlife in Kenya and Botswana - Sifuna, Nixon Wanyama (My University, 2010)
In both Kenya and Botswana, wildlife is a valuable natural resource in terms of its economic value, nutritional value, ecological value, medicinal value, educational and scientific value, as well as recreational and socio-cultural value. Despite this beneficial value, however, wild animals in both countries also cause damage and impose heavy losses on society. They also disrupt peaceful existence in local communities living in close proximity to wildlife areas. The damage they cause includes attacks on people and livestock, destruction of crops and other property as well as infrastructure. This has resulted in a human-wildlife conflict, with people having negative attitudes towards wildlife. Initially people seem to be the victims when wild animals attack them or destroy their property. Later, the animals are the real victims when people in retaliation start attacking, ensnaring or poisoning them. Contrary to the belief that it contributes to poverty alleviation, many people in the local communities in wildlife areas strongly believe wildlife has contributed to their poverty. Unless the governments of both Kenya and Botswana maintain efficient legal and institutional arrangements for wildlife damage, the future of wildlife conservation in both countries is bleak. These arrangements, if effectively enforced, have the potential to: reduce retaliatory killing of wildlife; ensure incidents of wildlife damage are reported; alleviate the losses and suffering associated with wildlife damage; and bolster public support for conservation programmes. It is encouraging that both countries recognize wildlife damage as a major problem and have put in place legal and institutional arrangements to address this problem. This study evaluated the legal and institutional arrangements in Kenya and Botswana on wildlife damage, assessing their suitability, adequacy as well as their effectiveness. While several studies have been conducted on wildlife damage, most of them mainly focus on institutional arrangements and the actual abatement measures adopted, few of them approach the subject from a legal standpoint, in the way this study does. Those studies do not, for instance, discuss the legal basis of the need for legal arrangements for wildlife damage alleviation and the various approaches and actual forms of legal intervention. This author through the use of semi-structured interviews, self-administered questionnaires, focus group discussions, and literature survey investigated the problem of ii wildlife damage in Kenya and Botswana. A central part of this investigation was on the types of damage, the animals involved, whether and how this problem has influenced public attitudes towards wildlife conservation, and suggestions for solution. Research for this study was conducted in the Laikipia region of Kenya and the Okavango delta region of Botswana between January and December 2006. This researcher interviewed 44 respondents from each country, comprising households from the local communities within wildlife areas, senior ranking government officials, leaders of NGOs that actually work on wildlife issues, experts in natural resource management as well as eminent scholars in environmental and natural resources law and policy. Research for this study established that while the governments of both Kenya and Botswana have established certain legal and institutional frameworks on wildlife damage, there are factors that hamper their efficient operation. These factors include the relevance and suitability of the existing laws, as well as their acceptability to stakeholders; lack of appropriate policy framewoks and dispute resolution mechanisms to support the regulatory regime; institutional problems such as overlapping responsibilities, lack of adequate resources and lack of motivation among staff. These factors together with others have continued to be a major challenge to the quest for appropriate and effective legal and institutional response to the problem of wildlife damage in both countries. The study found that in both countries the law vests in the state the power to manage wildlife wherever it occurs within the national boundaries. Botswana’s community-based wildlife management model, however, offers more incentives for conservation to local communities than Kenya’s state-centered system which largely disregards the role of local communities in wildlife matters. This author has argued that local communities are critical stakeholders and the success of any conservation programmes will depend on their goodwill. Besides, while the state has a duty to protect wildlife from harm by humans, it also has a corresponding duty to protect humans and their property from damage by wild animals and to ensure that wildlife does not undermine the people’s livelihoods and development. This is, however, not usually the case as in practice the state in both countries, and especially in Kenya, iii seems to favour wild animals at the expense of the people. The study has recommended certain reforms which need to be undertaken if Kenya and Botswana have to maintain appropriate and efficient legal and institutional arrangements on wildlife damage.
Keywords: Wildlife depredation; Kenya; Botswana; Compensation (Law)